Pengaruh Kepemimpinan Efektif Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Pada Kantor Camat Pondok Aren Kota Tangerang Selatan - Sindi Nurul Amanda; Sri Mulyani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the influence of effective leadership and non-physical work environment on employee performance at the Pondok Aren District Office in South Tangerang City. This research method used quantitative research methods. The data collection method used was a questionnaire survey. The population used in this study consisted of 90 employees. The sampling technique used saturated sampling, and obtained a sample of 90 respondents. Data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, correlation coefficient, simple linear regression, multiple linear regression, coefficient of determination, and hypothesis testing. The hypothesis testing partially on the variable of effective leadership (X1) obtained a calculated t-value > table t-value (6.974 > 1.987), which is also reinforced by a significance value of 0.000 < 0.05. This means that effective leadership (X1) has a significant effect on employee performance. Partial hypothesis testing of the non-physical work environment variable (X2) obtained a calculated t-value > table t-value (11.491 > 1.987), which is also reinforced by a significance value of 0.000 < 0.05. This means that the non-physical work environment (X2) has a significant effect on employee performance. Simultaneous hypothesis testing obtained a calculated t-value > table t-value (74.593 > 3.10), which is also reinforced by a significance value of 0.000 < 0.05. Thus, it can be said that effective leadership and the non-physical work environment simultaneously have a significant effect on employee performance. The coefficient of determination obtained an R Square value of 0.632, meaning that effective leadership and the non-physical work environment together contribute a 63.2% influence on employee performance. Keywords: Effective Leadership, Non-Physical Work Environment, Employee Performance.